Peningkatan Proses dan Hasil Belajar PJOK dengan Model Project Based Learning pada Peserta Didik Kelas V SD Negeri 62/II Padang Lalang - Duwi Lingga Oktavia; Deka Ismi Mori Saputra (CV. Master Literasi Indonesia, 2025)
This study began with a learning model that still used the lecture model, low student learning engagement in Physical Education (PJOK) subjects, and many PJOK scores were still below the Minimum Completion (KKM). This resulted in low student learning outcomes. This study aims to describe improvements in the learning process and outcomes in grade V of SD Negeri 62/II Padang Lalang This research is a classroom action research that examines the situation and conditions in the teaching and learning process at school. The subjects were 15 fifth-grade students of SD Negeri 62/II Padang Lalang. The research consisted of two cycles conducted by the researcher. Each cycle consisted of planning activities, action implementation, and observation and reflection. This research was conducted according to the academic calendar at SD Negeri 62/II Padang Lalang. Data were collected through observation, field notes, documentation, and test results. The results of the research data analysis indicate that the use of the Project Based Learning Model can improve the process and learning outcomes of Physical Education and Health in class V of SD Negeri 62/II Padang Lalang. This can be seen from the teaching process of educators in cycle I with an average of 71.2 while in cycle II with an average of 76.6. The same thing is also seen in student learning outcomes in cycle I 60.00%, and in cycle II it became 86.67%. Seeing the results of this study, classroom action research in the use of the Project Based Learning model in mathematics learning needs to be implemented and developed in order to improve the quality of education in the future.